Deliverable 6.18 Arctic Blue Economy and ocean observations. Costs and benefits - Buch, Erik (Zenodo, 2022)
The potential for growth of the Arctic Blue Economy is increasing due to climate change, fast technological development and strong demands from the global economy. Such development will however put severe stress on the vulnerable Arctic environment and there is a growing consciousness among nations surrounding the Arctic to ensure a responsible and sustainable development of Arctic Blue economy, which calls for a science-based management approach. Mandatory for such an approach is good knowledge and understanding of the Arctic Ocean environment and ecosystem,which demands a well-coordinated, integrated, sustained fit-for-purpose Arctic Ocean Observation System. The design of a proper Arctic Ocean Observation System is recommended to follow the concept outlined in the “Framework for Ocean Observations” (UNESCO, 2012). This will require a strong international coordination and governance structure responsible for dialog with users and stakeholders, sustained funding, maintenance of observation requirements (spatiotemporal resolution, quality, timeliness), technology development, free and open access to data. An important component of the design process is an assessment of the costs and value of the observing system i.e., justify that the benefit exceeds the costs. Costs are easier (although not unproblematic) to quantify than the benefits. OECD (Organisation for Economic Co-operation and Development) has in recent years, in cooperation with various ocean observing communities, started to establish ways to quantify the value of ocean observations and proposes some pragmatic approaches. It is therefore recommended that the management of the future Arctic Ocean Observation System works closely with experts from OECD on the establishment of a robust cost-benefit analysis methodology for the Arctic Ocean.